Educational tracking and social inequalities in long-term labor market outcomes: Six countries in comparison - Schindler Steffen; Bar-Haim Eyal; Barone Carlo; Birkelund Jesper Fels; Boliver Vikki; Capsada-Munsech Queralt; Erola Jani; Facchini Marta; Feniger Yariv; Heiskala Laura; Herbaut Estelle; Ichou Mathieu; et al. (SAGE Publications, 2025)
In this country-comparative study, we ask to what extent differentiation in secondary education accounts for the association between social origins and social destinations in adult age. We go beyond the widely applied formal definitions of educational tracking and particularly pay attention to country-specific approaches to educational differentiation. Our main expectation is that once we factor in these particularities, the degree to which educational differentiation accounts for social reproduction is quite similar across countries. Our analyses are based on national individual-level life-course data from six European countries that span from secondary education to occupational maturity. Our findings show that educational differentiation mediates the association between social origins and social destinations to a substantial degree in all countries. However, we still find some differences between countries in the extent to which educational differentiation accounts for social reproduction.